Travelers' Health Risk Perceptions and Protective Behavior: A Psychological Approach. (July 2017) - Chien, P. Monica; Sharifpour, Mona; Ritchie, Brent W.; Watson, Bernadette
Although the significance of travel health risks is well documented, the process through which people assess their vulnerability and ultimately take on preventive measures needs clarification. The purpose of this article is to better understand factors underlying travelers' health risk perceptions and their protective behavior. Using the health psychology literature, a conceptual model that incorporates multilevel psychological constructs was tested with 830 Australian outbound travelers. Worry was an important antecedent to both travel health risk perceptions and risk-protective behavior. Perceived control over health-related risks was not positively associated with risk perceptions but was positively associated with risk-protective behavior. Sensation-seeking propensity was negatively associated with risk perceptions but positively associated with risk-protective behavior. Travel risk perceptions mediated the relationship between the antecedents and risk-protective behavior. Implications for the design of health communication for industry and government are outlined, and future research avenues are also proposed.